A STUDY ON MAGNETIC RESONANCE IMAGING FISTULOGRAM EVALUATION OF PERIANAL DISCHARGE IN AN INDIAN POPULATION - Panda, Santosh Kumar; Panigrahi, Madhuri (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Pre-operative assessment of perianal fistulas is very important for best planning of surgery and prevention of relapse. The goal of magnetic resonance imaging (MRI) of perianal discharge is to demonstrate accurately the anatomy of the perianal region. MRI can clearly show the relationship of fistulas to the anal sphincter complex, levator plate, and the ischiorectal/ischioanal fossa. The aim of the study was to find out the various types of fistula and compare MRI fistulogram with surgery findings. Methods: In the present study, 38 number of patients were included who were sent for pre-operative MRI evaluation of perianal discharge and their post-operative data were collected for analysis. Surgical grading was according to Park’s surgical classification. Fistulas were graded in MRI according to St James’s University Hospital MRI classification of perianal fistulas. Results: It was found from the study that most of the patients were adults (35/38), whereas one was a child and one was adolescent. Almost all were male (36/38) except two were female. Around 50% of patients had previous history of surgery and had come for persistent/recurrent lesion. According to MRI, all except one had true fistula, rest one had sinus, and one had ischioanal abscess. Percentage of Grade I, Grade II, Grade III, and Grade IV fistula were 31.58, 13.16, 15.79, and 34.21, respectively. Percentage of intersphincteric (I and II) type was 44.74 (17 in no) and transsphincteric (III and IV) was 55.26 (21 in no.), and supra- and extra-sphincteric type was 0 in number. Most had internal anal canal opening posterior to transverse anal line, out of which most were around 6 o’clock position. MRI successfully described fistula tract in all except for two cases (36/38). Conclusion: MRI is very accurate in pre-operative evaluation and planning for surgery of perianal fistulas.